Students’ Difficulties in Using Nominal Sentences of Simple Present Tense at SMP Negeri 3 Duhiadaa - Hisasmaria Hisasmaria; Idrus Dama (Universitas Islam Darul Ulum Lamongan, 2025)
This study aims to investigate the difficulties faced by the students in using nominal sentences of simple present tense. the research was conducted at SMP Negeri 3 Duhiadaa with 20 students participating. The study employed a descriptive qualitative approach, with data collected through tests. The findings revealed that students struggled with constructing declarative, negative, and interrogative sentences, particularly with subject-verb agreement, verb forms, and sentence structure. The study also identified factors contributing to these difficulties, including limited practice, lack of understanding grammatical rules, and language interference. The results of this study can inform teaching practices and materials development to better support students in mastering nominal sentences of simple present tense.